Predictors of methotrexate response in Turkish children with oligoarticular and polyarticular juvenile idiopathic arthritis - Batu, Ezgi Deniz; Sönmez, Hafize Emine; Gülhan, Bora; Arıcı, Zehra Serap; Topaloğlu, Rezan; Bilginer, Yelda (The Turkish Journal of Pediatrics, 2017)
Methotrexate (MTX) is the most commonly used disease modifying anti-rheumatic drug in juvenile idiopathic arthritis (JIA). We aimed to define predictor factors for response to MTX in Turkish children with oligo- and polyarticular JIA. We reviewed the medical files of 59 oligo- and 57 polyarticular JIA patients seen in the clinic between May 2008 and May 2013 and who received MTX for ≥6 months. MTX responders were defined as having no/low disease activity according to juvenile arthritis disease activity score 71 (JADAS71) at 6 months after MTX initiation. Median age at JIA diagnosis/MTX initiation was 70/78 months. Involvement of the small or upper extremity joints at disease diagnosis and MTX initiation was more frequent; antinuclear antibody (ANA) positivity was less frequent; acute phase reactants, JADAS71 at MTX initiation, and the frequency of polyarticular subtype were higher in MTX non-responders. In multiple logistic regression, oligoarticular JIA subtype and ANA positivity were independent predictors of MTX response.